Flood discharge in the upper Mississippi river basin, 1993 - Parrett, Charles; Geological Survey (U.S.) (Denver : U.S Goverment Printing Office, 1993)
From mid-June through early August 1993, flooding was severe in the upper Mississippi River Basin following a wet-weather pattern that persisted over the area for at least 6 months before the flood. The magnitude and timing of several intense rainstorms in late June and July, combined with wet antecedent climatic conditions, were the principal causes of the flooding. Flood-peak discharges that equaled or exceeded the 10-year recurrence interval were recorded at 154 streamflow-gaging stations in the upper Mississippi River Basin. At 41 streamflow-gaging stations, the peak discharge was greater than the previous maximum known discharge. At 15 additional gaging stations, peak discharges exceeded the previous maximum regulated peak discharge. At 45 gaging stations, peak discharges exceeded 100-year recurrence intervals.
Keywords: Floods -- Mississippi River Valley; Floods -- Missouri River Valley; Flood damage -- Mississippi River Valley